Cerebellar impairments in genetic models of autism spectrum disorders: A neurobiological perspective - Yenkoyan, Konstantin; Grigoryan, Artem; Kutna, Viera; Shorter, Susan; O'Leary, Valerie B; Asadollahi, Reza; Ovsepian, Saak V (Progress in neurobiology, 2024)
Functional and molecular alterations in the cerebellum are among the most widely recognised associates of autism spectrum disorders (ASD). As a critical computational hub of the brain, the cerebellum controls and coordinates a range of motor, affective and cognitive processes. Despite well-described circuits and integrative mechanisms, specific changes that underlie cerebellar impairments in ASD remain elusive. Studies in experimental animals have been critical in uncovering molecular pathology and neuro-behavioural correlates, providing a model for investigating complex disease conditions. Herein, we review commonalities and differences of the most extensively characterised genetic lines of ASD with reference to the cerebellum. We revisit structural, functional, and molecular alterations which may contribute to neurobehavioral phenotypes. The cross-model analysis of this study provides an integrated outlook on the role of cerebellar alterations in pathobiology of ASD that may benefit future translational research and development of therapies.
Keywords: Autism spectrum disorders; Autism Spectrum Disorder; Animals; Disease Models, Animal; Tsc1/2; Purkinje neurons; mozeček; Fmr1; Cerebellum; modely nemocí na zvířatech; Mecp2; modely genetické; poruchy autistického spektra; Models, Genetic; zvířata; Nlgn3/4